1993
DOI: 10.1152/physrev.1993.73.3.617
|View full text |Cite
|
Sign up to set email alerts
|

Replicative senescence of human fibroblast-like cells in culture

Abstract: The life history of fibroblast and fibroblast-like cells includes an initial stage of outgrowth and establishment in culture; a period of vigorous proliferation which has a variable length, depending on the tissue of origin, age of the donor, etc.; a period of declining proliferative vigor which includes substantial cell death; and finally, the emergence of an (apparently) long-lived population which is unable to proliferate in response to growth factors. During the phase of declining proliferative vigor, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
138
2
11

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(158 citation statements)
references
References 0 publications
7
138
2
11
Order By: Relevance
“…Rather, senescent cells adopt a complex phenotype that entails many changes in gene expression (Cristofalo and Pignolo, 1993;Campisi et al, 1996;Faragher, 2000;Krtolica and Campisi, 2002). In addition to imposing a block to cell cycle progression, the senescence response causes changes in cell morphology (generally, adoption of an enlarged flattened shape).…”
Section: The Senescent Phenotypementioning
confidence: 99%
“…Rather, senescent cells adopt a complex phenotype that entails many changes in gene expression (Cristofalo and Pignolo, 1993;Campisi et al, 1996;Faragher, 2000;Krtolica and Campisi, 2002). In addition to imposing a block to cell cycle progression, the senescence response causes changes in cell morphology (generally, adoption of an enlarged flattened shape).…”
Section: The Senescent Phenotypementioning
confidence: 99%
“…Early ideas proposed that, because senescent cells are incapable of self-renewal, cellular senescence might cause or contribute to aging phenotypes such as immune failure, poor would healing, skin atrophy, the decline gastrointestinal function, and so forth -phenotypes that are presumed to arise owing to a loss of cell proliferative (and hence tissue regenerative) capacity. These ideas arose primarily because the first stimulus that was recognized to cause cellular senescence was repeated cell division (replicative senescence) (Cristofalo and Pignolo, 1993;Campisi et al, 1996;Smith and Pereira-Smith, 1996). Subsequent studies showed that replicative senescence is caused, in large measure, by the progressive shortening of telomeres that occurs with each cell cycle in cells that do not express the enzyme telomerase (Levy et al, 1992;Bodnar et al, 1998;Shay and Wright, 2001).…”
Section: Cellular Senescencementioning
confidence: 99%
“…The finite replicative lifespan of normal cells in culture is thought to result from multiple environmental and genetic mechanisms (3) and is frequently used as one model of human aging. Supporting the usefulness of this model, several laboratories, by using different types of normal human cells maintained in culture, have presented evidence for a negative correlation between donor age and proliferative lifespan in vitro (4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%